PENGARUH CITRA MEREK DAN KUALITAS PRODUK TERHADAP LOYALITAS PELANGGAN SALBUTAMOL NEBULES - Rahmadi Rahmadi (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2017)
This study aims to know the degree of Brand Image and Product Quality either partially or simultaneously towards Customer Loyalty of Salbutamol Nebules in Bandung. This research was descriptive and verificative. Method used was survey and by applying SPSS program.Purposive sampling technique was taken by mean of questionnaires. Total sample of 88 respondents picked. The result showed that all independent variables were affected significantly and positive to the Customer Loyalty.Key words : Brand Image, Product Quality and Customer Loyalty